PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERBASIS EKONOMI KREATIF DI LAPAK PESONA - Erni Andayani; Dendy Eta Mirlana; Anton Subagyo (Universitas 17 Agustus 1945 Samarinda, 2023)
Micro, Small and Medium Enterprises (MSMEs) are productive businesses owned by individuals or business entities that meet the criteria to become micro-enterprises. MSMEs do play a role in reducing the increasing poverty rate in Indonesia. MSMEs have a role in fighting poverty by utilizing the potential of natural resources that are managed comprehensively. This research examines creative economy-based MSME development strategies in Lapak Pesona, Village of Madiun Lor, Manguharjo District, Madiun City. The purpose of the study is to find out the challenges and obstacles faced by creative economy MSMEs in Lapak Pesona in developing their businesses. The research type used in this research is a qualitative research method and uses proportional sampling, namely a sampling technique by first determining the data source. Data collection techniques are carried out directly through observation, interviews and documentation. The results of the research obtained found that business actors in Lapak Pesona still find it difficult to develop their businesses to grow. The challenges and obstacles are limited capital and lack of promotional facilities. Using appropriate strategic planning and problem solving methods can make it easier to resolve the problems faced. One of the best ways to use is to utilize the methods provided through a series of stages in the SWOT analysis